Giving Celery Leaf Boiled Water in Lowering Blood Pressure in the Elderly with Essential Hypertension - Donsu, Jenita Doli Tine; Hapsari, Ayu Putri; Palestin, Bondan (GLOBAL HEALTH SCIENCE GROUP, 2024)
One of the non-communicable diseases is a cardiovascular disease that causes the 5th highest death in Indonesia, characterized by a person's condition of having an abnormal increase in blood pressure in the arteries. This study was to determine the administration of celery leaf decoction water in lowering blood pressure in the elderly with essential hypertension in Sidoluhur village, the working area of the Godean I Health Center, Sleman Regency. The type of quantitative with a quasi-experimental approach of pretest-posttest control group design 2 groups on February 6-March 02, 2024 for the elderly with essential hypertension. The data collection techniques carried out by the researcher using primary data and secondary data totaling 110 respondents and data analysis using the wilcoxon sign rank test. The pre-test intervention group had morning systolic blood pressure 154.40 mmHg, morning diastolic blood pressure 79.86 mmHg. The average blood pressure of the elderly on the post-test 145.98 mmHg, afternoon systolic blood pressure and afternoon diastolic blood pressure 89.91 mmHg. The control group pre-test 152.32 mmHg morning systolic blood pressure, morning diastolic blood pressure 81.73 mmHg. The average blood pressure of the elderly in the post-test 144.78 mmHg, afternoon systolic blood pressure and afternoon diastolic blood pressure 85.80 mmHg. The results of bivariate analysis of the intervention group with a p-value of <0.05 and a control group with a p-value of <0.05. There is an effect of giving celery leaf boiled water on lowering blood pressure in the elderly with essential hypertension.